2013
DOI: 10.1007/s11060-013-1133-3
|View full text |Cite
|
Sign up to set email alerts
|

Promoter methylation of AREG, HOXA11, hMLH1, NDRG2, NPTX2 and Tes genes in glioblastoma

Abstract: Epigenetic alterations alone or in combination with genetic mechanisms play a key role in brain tumorigenesis. Glioblastoma is one of the most common, lethal and poor clinical outcome primary brain tumors with extraordinarily miscellaneous epigenetic alterations profile. The aim of this study was to investigate new potential prognostic epigenetic markers such as AREG, HOXA11, hMLH1, NDRG2, NTPX2 and Tes genes promoter methylation, frequency and value for patients outcome. We examined the promoter methylation s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
22
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(26 citation statements)
references
References 34 publications
3
22
1
Order By: Relevance
“…Further survival analysis in this study, in which we included tumors of different malignancy grade, demonstrated significant correlation between NDRG2 promoter methylation and poor patient outcome (Figure 1B). This is in contrast to earlier findings 5, 22, where studies on NDRG2 promoter methylation and patient survival have been done with the focus on glioblastoma alone.…”
Section: Discussioncontrasting
confidence: 94%
See 1 more Smart Citation
“…Further survival analysis in this study, in which we included tumors of different malignancy grade, demonstrated significant correlation between NDRG2 promoter methylation and poor patient outcome (Figure 1B). This is in contrast to earlier findings 5, 22, where studies on NDRG2 promoter methylation and patient survival have been done with the focus on glioblastoma alone.…”
Section: Discussioncontrasting
confidence: 94%
“…With particular regard to glioma, recent clinical studies demonstrated NDRG2 as a putative tumor suppressor gene silenced in the majority of glioblastomas 5, 7, 22. However, the main mechanism that underlies NDRG2 silencing in glioma is unknown.…”
Section: Introductionmentioning
confidence: 99%
“…Progression free survival (PFS) was also higher among methylated than among unmethylated patients (13.3 months vs. 7.8 months) [95]. This is in agreement with results of another study that showed MGMT methylation was correlated with better survival of treated GBM patients with a hazard ratio (HR) of 0.61 [96]. Moreover the median OS among GBM patients with methylated MGMT promoter tumors was 19 months compared with 13 months in patients with unmethylated MGMT promoter tumors and the median PFS was 8 months for the methylated MGMT promoter status compared with 6 months for the unmethylated MGMT promoter status [97].…”
Section: Dna Repair Gene Methylation Status As Biomarkersupporting
confidence: 87%
“…Two sets of primers targeting the CpG island near the transcription start site in the promoter region of HOXA11 [12] were employed to evaluate the methylation status in naive MCF-7 and MDA-MB-231 cells (Figure 2A). The promoter region was completely methylated in MDA-MB-231 cells and partially methylated in MCF-7 cells.…”
Section: Resultsmentioning
confidence: 99%
“…The methylated primers were as follows: forward primer, 5′-GTTTACGGTGTTATAGAAATTGGAC-3′; reverse primer, 5′-GTACACAAAAACTACCTACAAACGC-3′; product length, 129bp. The unmethylated primers were as follows: forward primer, 5′-TTTATGGTGTTATAGAAATTGGATGA-3′; reverse primer, 5′-TCATACACAAAAACTACCTACAAACAC-3′; product length, 130bp [12]. A total of 35 cycles were run with an annealing temperature of 55°C.…”
Section: Methodsmentioning
confidence: 99%